2016
DOI: 10.21037/jtd.2016.11.08
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of farnesoid X receptor in small airways contributes to epithelial to mesenchymal transition and COX-2 expression in chronic obstructive pulmonary disease

Abstract: Background: Epithelial-mesenchymal transition (EMT) and cyclooxygenase-2 (COX-2) contribute to airway remodelling and inflammation in chronic obstructive pulmonary disease (COPD). Recent data suggest that the farnesoid X receptor (FXR), a nuclear receptor traditionally considered as bile acid-activated receptor, is also expressed in non-classical bile acids target tissues with novel functions beyond regulating bile acid homeostasis. This study aimed to investigate the potential role of FXR in the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similar to the EMT-suppressing effect in our results ( Figure 4 and Figure 5 ), GS decreases motility and invasion of pancreatic cancer cells [ 26 ]. GW4064 enhances and GS inhibits EMT changes in TGF-β-treated human bronchial epithelial cells [ 27 ], and bile acids, including CDCA, also induce EMT in human lung alveolar cells [ 28 ]. Interestingly, lithocholic acid, which is a weak FXR agonist [ 3 ], stimulates TGF-β release from lung fibroblasts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the EMT-suppressing effect in our results ( Figure 4 and Figure 5 ), GS decreases motility and invasion of pancreatic cancer cells [ 26 ]. GW4064 enhances and GS inhibits EMT changes in TGF-β-treated human bronchial epithelial cells [ 27 ], and bile acids, including CDCA, also induce EMT in human lung alveolar cells [ 28 ]. Interestingly, lithocholic acid, which is a weak FXR agonist [ 3 ], stimulates TGF-β release from lung fibroblasts [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the IL-1 β /COX-2 signaling pathway can cause airway mucus hypersecretion in COPD [ 18 ]. Inflammatory factors bind to corresponding receptors to activate COX-2, leading to increased secretion [ 19 ]. Airway mucus hypersecretion in COPD is related to an inflammatory reaction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al reported that CS exposure leads to iNOS expression, which results in production of toxic NO metabolites, leading to severe lung damage (29). The levels of COX-2 are significantly increased in small airway epithelium of patients with COPD, and the increase in the levels of this molecule contribute to airway remodeling and inflammation, which are major characteristics of COPD (30). Therefore, inhibition of iNOS and COX-2 may be important for reducing airway inflammation.…”
Section: Discussionmentioning
confidence: 99%